2013
DOI: 10.1111/ger.12104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sodium hypochlorite as a denture cleanser: a clinical study

Abstract: The 0.5% NaOCl solution was effective in reducing microorganisms without significant changes in colour or roughness of denture resin. The participants reported satisfaction with the cleaning results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
3
21

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(98 citation statements)
references
References 39 publications
3
71
3
21
Order By: Relevance
“…This result may be explained by the fact that immersion in hypochlorite solutions did not cause significant changes on surface roughness of acrylic resins (4,5,(13)(14)(15). The present results indicate that this property was not altered by this solution even when employed in association to brushing.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…This result may be explained by the fact that immersion in hypochlorite solutions did not cause significant changes on surface roughness of acrylic resins (4,5,(13)(14)(15). The present results indicate that this property was not altered by this solution even when employed in association to brushing.…”
Section: Discussionmentioning
confidence: 46%
“…This solution was employed due to its low cost, accessibility and efficacy (4,5). This immersion procedure corresponded to an exposition of a daily cleaning of 20 min for 365 days, totaling 121 h and 30 min of immersion.…”
Section: Denture Hygiene Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,16 İdeal bir protez temizleyici ajan, protez kaidesi ve yapay dişlerin mekanik özelliklerine zarar vermeden biyofilm birikimini azaltmalı, bakterisidal ve fungisidal etkiye sahip olmalıdır. 6 Elde edilen veriler SPSS 15.0 (SPSS Inc., Chicago, IL, Amerika Birleşik Devletleri) programına aktarılarak tanımlayıcı istatistikleri yapıldı. Grup içi karşılaştırmalar eşleştirilmiş örneklemler t-testi kullanıla-rak yapıldı (p<0.05).…”
Section: Discussionunclassified
“…NaOCl solution that also used in the present study in the concentration of 5%, dissolves mucin, organic substances and shows antimicrobial activity by the action of hydroxyl ions and chloramination 20,29) . Several studies have reported satisfactory results for the antimicrobial activitiy of NaOCl solutions with different concentrations on denture base materials [30][31][32] . However, NaOCl has some disadvantages on denture base materials such as discoloration and an increase in surface roughness, depending on the concentration and immersion time 17,[33][34][35] .…”
Section: Discussionmentioning
confidence: 99%